1990
DOI: 10.2307/1940260
|View full text |Cite
|
Sign up to set email alerts
|

Patch‐Size Effects on Early Succession in Southern Appalachian Forests

Abstract: Four sizes of forest opening (0.016, 0.08, 0.4, 0.4, and 2.0 ha; two replicates each) were established in a Southern Appalachian forest to examine the effects of disturbance size on earl successional community structure and function. Solar radiation, soil temperature, and air temperature were all higher in large openings than small openings and increased from edge to center of disturbance patches. Aboveground net primary productivity (NPP) was 3—4 times as highe in larger (2.0 ha) as small (0.016 ha) openings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 30 publications
(47 reference statements)
8
109
0
1
Order By: Relevance
“…The gaps have thus a positive effect on the diversity of shade tolerant species and light-requiring species, at least some years after disturbance. The lack of change for the other resource requirements of the plant community was unexpected as many studies have shown a change of resources within the gaps when directly measured [10,45,56]. In our case (a forest without water deficit or water surplus), the lack of variation for water needs suggested that the different species may find their water requirements in the gaps.…”
Section: Species Richness and Species Profilementioning
confidence: 58%
See 1 more Smart Citation
“…The gaps have thus a positive effect on the diversity of shade tolerant species and light-requiring species, at least some years after disturbance. The lack of change for the other resource requirements of the plant community was unexpected as many studies have shown a change of resources within the gaps when directly measured [10,45,56]. In our case (a forest without water deficit or water surplus), the lack of variation for water needs suggested that the different species may find their water requirements in the gaps.…”
Section: Species Richness and Species Profilementioning
confidence: 58%
“…The effect of canopy gaps on the environmental factors is also quite well known [10,45,56]. Forest gaps are characterized by a strong change of many factors such as air and soil temperatures, air and soil moistures, irradiance, wind speed and soil properties (e.g., humus mineralization and humification) [10,45,56]. The resource availability (light, water and nutrients) increases with disturbances [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Regeneration gaps created by this method can emulate the northern hardwood disturbance regime, which is characterized by small fires, windthrow and natural senescence (Borman and Likens 1979, Runkle 1981, Canham and Loucks 1984, Whitney 1986, Frelich and Lorimer 1991. The effects of group selection on regeneration have been documented in Eastern Canada (Hatcher 1966), northeastern (Marquis 1965, Leak and Filip 1977, McClure and Lee 1993, Smith and Ashton 1993 and central United States (Phillips and Shure 1990, Dale et al 1995, Weigel and Parker 1997. Among these studies, only Smith and Ashton (1993) mentioned the effects of regeneration gaps (45 m) on white pine regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The increased availability of light, water, and nutrients in gaps increases plant diversity and net primary productivity and encourages the growth and regeneration of less shade tolerant species (Bormann and Likens 1979, Boring et al 1981, Brokaw 1982, Phillips and Shure 1990, Wilder et al 1999. Predicting the response of herbivorous insects to such complicated and dynamic environments is difÞcult and quickly confounded by factors such as gap size and age.…”
mentioning
confidence: 99%
“…In many forests, canopy gaps created by treefalls, wind damage, and other minor events serve as important centers of plant growth and succession (Runkle 1981, White et al 1985, Phillips and Shure 1990, Clinton et al 1993. The increased availability of light, water, and nutrients in gaps increases plant diversity and net primary productivity and encourages the growth and regeneration of less shade tolerant species (Bormann and Likens 1979, Boring et al 1981, Brokaw 1982, Phillips and Shure 1990, Wilder et al 1999.…”
mentioning
confidence: 99%